1994
DOI: 10.1007/bf03015624
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and EEG changes during rapid-sequence induction of anaesthesia

Abstract: The relationship between the changes in haemodynamic function and the electroencephalogram (EEG) during rapidsequence induction of anaesthesia was studied in 15 ASA I patients. Anaesthesia was induced with a bolus thiamylal (5 mg" kg -l iv)followed by succinylcholine (1 mg" kg-~). Tracheal intubation was attempted one minute after the injection of suc Aprds lfntubation trachdale, la PAs augmente de 44% au dessus de la valeurs post-induction (P < 0,05) et en m~me temps I'AE augmente~ 13,1 Hz (P < O, 05). En con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Since laryngoscopy and endotracheal intubation, similar to any other peripheral noxious stimulus, might produce a reflex response in the reticular activating system of brainstem, it can lead to wakefulness, making the planes of anaesthesia lighter. [ 11 ] Hence, maintaining the BIS values at 40–50 during the induction of anaesthesia may prevent such responses.…”
Section: Discussionmentioning
confidence: 99%
“…Since laryngoscopy and endotracheal intubation, similar to any other peripheral noxious stimulus, might produce a reflex response in the reticular activating system of brainstem, it can lead to wakefulness, making the planes of anaesthesia lighter. [ 11 ] Hence, maintaining the BIS values at 40–50 during the induction of anaesthesia may prevent such responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, peripheral noxious stimuli reach the brain through the ascending reticular activating systems of the brain stem [16]. Mi et al [3] reported that BIS was significantly increased by laryngoscopy and intubation during the infusion of propofol with or without fentanyl pretreatment.…”
Section: Discussionmentioning
confidence: 99%